Perception Analysis Of Health Workers' Stress During the Covid-19 Pandemic - Heriziana Heriziana; Santi Rosalina (Eduvest - Journal of Universal Studies, 2022)
The COVID-19 pandemic has had a profound effect on all aspects of society, including mental health and physical health. WHO and public health authorities around the world are acting to control the COVID-19 outbreak. However, this time of crisis creates stress throughout the population. Fear and anxiety about this new disease, plus other factors can influence job stress. The type of research used is correlation research. This research was conducted at X Hospital in South Sumatra 2021. The population of this study was all health workers at Hospital X in South Sumatra 2021, totaling 382 people based on staffing data for Hospital X in South Sumatra as of March 2021. The sample of this study that will be examined using the slovin formula, which amounts to 80 health workers at the hospital. Pain X in South Sumatra. Based on the results and discussion, it can be concluded that: The company's regulation (X1) has a significance value of 0.743 > 0.05, which means that the company's regulation (X1) has no effect on stress symptoms (Y). Anxiety (X2) has a significance value of 0.461 > 0.05, which means that worry (X2) has no effect on symptoms of stress (Y). Workload (X3) a significance value of 0.007 <0.05, it means that there is an effect of workload (X3) on stress symptoms. Working conditions (X4), a significance value of 0.023 <0.05, it means that there is an effect of working conditions (X4) on symptoms of stress.